Application of the Fenton Process in the Petroleum Refinery Spent Caustic Wastewater Treatment - Rahmanisa, Riang Anggraini; Widiasa, I Nyoman (Reaktor, 2020)
Spent caustic wastewater is produced from the scrubbing process using a caustic solution to absorb contaminants in the oil stream (hydrocarbon). Indonesia’s Petroleum Oil Refinery produces spent caustic wastewater from LPG and kerosene processing unit. Spent caustic wastewater has the characteristic of a strong odor with very high pH (12-14), containing dangerous pollutants such as phenol, aldehydes, mercaptans, and thiols that can be harmful to the human and environment. The Fenton process is used to treat spent caustic before being discharged to the environment. The Fenton process is one of AOPs (Advanced Oxidation Process) using Fe2+ as a catalyst and H2O2 as an oxidant to oxidize organic contaminants in wastewater. This study aims to determine the operating conditions of the Fenton Process with the target characteristics of treated spent caustic meet the WWTP (Waste Water Treatment Plant) inlet specifications and to make the design process of spent caustic treatment with the Fenton Process capacity of 10 m3/day. By operating at the H2O2/Fe (II) ratio of 1.8, the final target was achieved with COD of 810 ppm, ammonia of 22.84 ppm, sulfide of 60.93 ppm and phenol of 14.56 ppm. Total Capital Investment (TCI) for the design is US$ 2146701.89 whereas Total Manufacturing Cost of US$ 2089740.75.Keywords: spent caustic; refinery wastewater; Fenton process